Nanoparticles for Inducing Antigen-Specific T Cell Tolerance in Autoimmune Diseases - Benne, Naomi; ter Braake, Daniëlle; Stoppelenburg, Arie Jan; Broere, Femke (Frontiers in Immunology, 2022)
Autoimmune diseases affect many people worldwide. Current treatment modalities focus on the reduction of disease symptoms using anti-inflammatory drugs which can lead to side effects due to systemic immune suppression. Restoration of immune tolerance by down-regulating auto-reactive cells in an antigen-specific manner is currently the “holy grail” for the treatment of autoimmune diseases. A promising strategy is the use of nanoparticles that can deliver antigens to antigen-presenting cells which in turn can enhance antigen-specific regulatory T cells. In this review, we highlight some promising cell targets (e.g. liver sinusoidal endothelial cells and splenic marginal zone macrophages) for exploiting natural immune tolerance processes, and several strategies by which antigen-carrying nanoparticles can target these cells. We also discuss how nanoparticles carrying immunomodulators may be able to activate tolerance in other antigen-presenting cell types. Finally, we discuss some important aspects that must be taken into account when translating data from animal studies to patients.